Darbuotojų profesinio ugdymo sąnaudos ir jų valdymas - Mackevičius, Jonas; Subačienė, Rasa (Information & Media, 2008)
Darbuotojų profesinio ugdymo sąnaudų valdymo problema yra labai aktuali dinamiško ir konkurencingo verslo sąlygomis. Sprendžiant šią problemą tiesiogiai susiduria įmonių vadovų ir darbuotojų interesai: įmonių vadovai, stengdamiesi mažinti darbuotojų profesinio ugdymo sąnaudas, gali prarasti visus geriausius savo specialistus. Straipsnyje nagrinėjama darbuotojų profesinio ugdymo reikšmė ir būtinumas visuotinės rinkos ekonomikos sąlygomis, pateikiama informacijos apie darbuotojų profesinio ugdymo sąnaudų formavimo sistemą ir šios informacinės sistemos valdymo būdus. Pirmą kartą pateikiama į penkias grupes suskirstyta darbuotojų profesinio ugdymo sąnaudų klasifikacija: 1) darbuotojų priėmimo į darbą, 2) orientavimo, 3) darbo mokymo, 4) papildomo mokymo ir 5) darbuotojų išėjimo sąnaudų. Rekomenduojama darbuotojų profesinio ugdymo sąnaudų valdymo sistema, kurią sudaro šie elementai: 1) planavimas, 2) buhalterinė apskaita, 3) analizė ir kontrolė, 4) prognozavimas. Šie elementai, siekiant priimti optimalius darbuotojų profesinio ugdymo sąnaudų valdymo sprendimus, straipsnyje nagrinėjami smulkiau.The expenditure of personnel vocational training and their managementJonas Mackevičius, Rasa SubačienėSummaryThe problem of management of expenditure of personnel vocational training is topical in dynamic and competitive business circumstances; however it is not investigated fairly. In the process of analysis it is determined, that legislation of the Republic of Lithuania and different authors use dissimilar definitions. Mostly denominated training in-service or educational expenditure, besides there are represented different their composition. Actually, for more effective management of expenditure of personnel vocational training, it is a proposal to classify them into five groups: 1) acceptance of personnel, 2) orientation, 3) working teaching, 4) additional teaching, 5) discharge of personnel. The expenditure ascribed by each group is represented in the article. Standard system of management of expenditure of personnel vocational training is created. It consists of four basic elements: planning, accounting, analysis and control, forecasting. In the process of planning it is offered to take into account levels of personnel competence. For more effective accounting system of expenditure of personnel vocational training, it is offered to separate additional accounts: 60033 “For direct costs attached expense of personnel vocational training”, 60043 “For indirect costs attached expense of personnel vocational training”, 61032 “Expenditure of sale personnel vocational training”, 61142 “Expenditure of management personnel vocational training”. Analysis of expenditure of personnel vocational training it is offered to do by following phases: analysis of dynamic, analysis of structure, analysis of influence to profitability. Forecasting of expenditure of personnel vocational training it is offered to make according the phases of their evaluation.